Implementasi Metode Saintifik pada Mata Pelajaran al-Qur’an Hadits Kelas XI IPS di Madrasah Aliyah Negeri Lamongan - Manan, Abdul; Imron, Muhammad (Universitas Islam Lamongan, 2020)
This thesis is the result of field research to answer the question: How the Scientific Method Implementation Subjects Qur'an Hadith Class XI IPS in Madrasah Aliyah Negeri Lamongan, How Supporting and Inhibiting factors in the implementation of the Scientific Method Subjects Al -Qur'an Hadith Class XI IPS in Madrasah Aliyah Negeri Lamongan, How to Overcome Obstacles to the Implementation of the Scientific method Subjects Qur'an Hadith Class XI IPS in Madrasah Aliyah Negeri Lamongan.This research is a qualitative descriptive study in which research methods using the method of observation, interviews and documentation, The steps of analysis techniques in this study, namely Data Reduction (Data Reduction), Display Data (Data Display) and Data Verification.The results of this study concluded that the implementation of the Scientific Method 5M steps: Observe, ask, Trying, Associate and Communicating. Factors supporting the implementation of the scientific method is the mental attitude of educators, the ability of educators, instructional media were insufficient, library, facilities eligible, the school environment is conducive and the inhibiting factor is telatnya pengkontribusian books, difficulty adjusting material, method is emerging, assessment still sophisticated, learning tools, school hours are so dense, the difficulty in dealing with differences in the characteristics of learners, difficulties in obtaining resources and tools for learning, difficulties in conducting the evaluation and setting time. To overcome the inhibiting factor is by no delays in the contribution of the book, the agency held a workshop on learning as much as possible by means of the scientific method, assessment and learning how to manufacture the device, division of rest time.In line with the above conclusions, then to the academic community Madrasah Aliyah Negeri Lamongan in order to implement the scientific method as well as possible.